Playing Pattern Analysis of Men’s Single Badminton Matches - Fadhil Abdullah, Mohd; Janep, Mandra; Shahrul Azzfar, Mohamad; Abd Karim, Zulakbal; Rahmat, Azali; Md Nadzalan, Ali (International Journal of Engineering and Technology, 2018)
The objective of this study is to determine the playing pattern of selected menâ€™s single badminton matches during BWF World Championships 2017. Playersâ€™ return methods; smash, drop, drive, lob, clear and net performed in the match were notated using notational analysis. The return methods were also analysed based on the place of target; fore left, fore right, mid left, mid right, rear left and rear right. The non-effective returns were also notated. The findings of the playing patterns performed by players are important as this can be used as a source of reference for the players to plan on technical and tactical part during the real match especially in important tournament.Â